The Efficacy Strategy of the Launching New Variety Product: Case Study Bagong Canned Gudeg a Traditional Foods from Yogyakarta - Tommy Hendrix; Syukri Yusuf Nasution (Jurnal Manajemen Indonesia, 2022)
Nowadays, culinary industries significantly enhance capacity product diversification to endorse economic development. This significant change appears to unlock the product's positioning in the market through various foods industries. Also, R & D results often become a solution for fostering the movement of creative industries to appear. Food canning technology has enough potential to be developed as an appropriate production process, increased market share, attractive packaging that consumers prefer, and an affordable price. In the case study, we used the trademark Bagong with five tastes as product industry as traditional foods from Yogyakarta. The purpose of this paper conducted to find the efficacy strategy for launching the product Bagong Canned Gudeg. As one of the flagship products of traditional food with a high taste derived from the recipes of ancestral people of Yogyakarta based on the development of technology R & D results. The method performed with qualitative data using Test Product Preferences (Organoleptic Test) to understand consumers' level of Bagong Canned Gudeg with 5 product variants on various attributes, market segmentation, and in-depth interviews have engaged in the business canned gudeg owner and company management with 74 respondents from Bandung, Bogor, and Yogyakarta area. This study indicates that based on the marketing analysis results, the products developed worthy of being marketed and received positive results from the consumers (respondents). Keywords— Bagong Canned Gudeg; Case Study; Efficacy Strategy; Launching New Product; Traditional Foods